New clerodane diterpenoids from the twigs and leaves of Croton euryphyllus. Issue 6 (15th March 2015) - Pan, Zhenghong; Ning, Desheng; Wu, Xingde; Huang, Sisi; Li, Dianpeng; Lv, Shihong
Graphical abstract: Abstract: Three new nor-clerodane diterpenoids, crotoeurins A–C (1 –3 ), together with four known ones were isolated from the twigs and leaves of Croton euryphyllus . Among them, crotoeurin A (1 ) is a new nor-clerodane diterpenoid dimer with a unique cyclobutane ring via a [2+2] cycloaddition. Their structures were elucidated by spectroscopic analyses and the stereochemistry of1 was confirmed by single-crystal X-ray diffraction analysis. Compounds1 –3 exhibited neurite outgrowth-promoting activity on NGF-mediated PC12 cells at concentration of 10 μM.